Agricultores familiares e diversificação em áreas de cultivo de tabaco: o caso de Monte Castelo/SC - Uba, Daniel (2012)
The Framework Convention on Tobacco Control, promulgated by the World Health Organization, in 2003, internationalized the tobacco consumerism, commercialization and production problem. To comply with the Articles 17 and 18 from the Framework Convention, Brazil created the National Program for Diversification in Tobacco Cultivated Areas (Programa Nacional de Diversificação em Áreas com Cultivo de Tabaco) aiming at supporting rural development actions to motivate family farmers to accede to the productive diversification proposals in the tobacco production regions. The objective of this thesis was to analyze the strategies employed by the federal government to ensure legitimacy in the incentive process to the productive diversification in the city of Monte Castelo, in the state of Santa Catarina, highlighting its repercussions on local agents` actions and family farmers` choices, tobacco producers. The research was developed from a case study, accomplished in Monte Castelo/SC, with a qualitative approach. The methodological procedures used for data collection combined the bibliographical research, documental research and semi-structured interviews, directed to rural development agents and family farmers, both those who joined the diversification, and those who decided to remain in tobacco production. As Brazil is a tobacco producer, issues related to the impacts of the Framework Convention adoption by family farmers have a significant role in the negotiation agenda. In Monte Castelo, the social agents` relation with the tobacco agroindustry is greater than the relation with the National Program, reflecting on the meanings ascribed to the diversification notion by institutions and on the development actions presented to family farmers. To family farmers, diversification is understood as the presence of multiple activities developed in the property, practiced along generations. It can be concluded that the accession to the diversification proposals is related to the advantages that a new activity offers in relation to what is already available to the producer by the agroindustry integration system. However, the safety provided by the agroindustry integration system encourages family farmers to continue tobacco production in Monte Castelo.